Analisis Peran Pemerintah Desa dalam Pengelolaan Pembangunan untuk Peningkatan Desa Sungai Malaya Kecamatan Sungai Ambawang Kabupaten Kubu Raya - Yunita, Nurma; Firayanti, Yuni; Mahardika, Tubagus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Village development is a key pillar in promoting community welfare at the local level. However, the implementation of development programs often faces challenges, particularly in planning, execution, and community participation. This research was conducted in Sungai Malaya Village, Sungai Ambawang Sub-district, Kubu Raya Regency, to analyze the role of the village government in managing development. The main objective of this study is to determine the effectiveness of the village government's role in improving the quality of development, identify supporting and inhibiting factors, and assess the level of community participation in the process. The research uses a descriptive qualitative approach, with data collection techniques including interviews, observations, and documentation. Informants include the village head, village officials, community leaders, and local residents. The findings indicate that the village government plays a significant role in planning and implementing development, especially in infrastructure sectors such as roads, clean water, and health facilities. Community involvement through village meetings (Musyawarah Desa) is a key factor in the success of development programs. However, challenges such as limited funding and uneven development across village areas remain. This study contributes to the understanding of participatory and accountable village governance. Enhancing the capacity of village officials and increasing engagement with community groups, including youth and women, is essential for sustainable development. Future research is recommended to explore the effectiveness of village budget management using quantitative methods.